POT1 mutations are frequent and associated with Ki-67 index in canine diffuse large B-cell lymphoma - Fanelli, Antonella; Marconato, Laura; Licenziato, Luca; Minoli, Lucia; Rouquet, Nicole; Aresu, Luca (Frontiers in Veterinary Science, 2022)
Diffuse large B-cell lymphoma (DLBCL) represents one of the most frequent and deadliest neoplasia in dogs worldwide and is characterized by a remarkable degree of clinical heterogeneity, with poor chances to anticipate the outcome. Even if in the last years some recurrently mutated genes have been identified, the genetic origin of canine DLBCL (cDLBCL) is not yet completely understood. The aim of the present study was to assess the prevalence of POT1 mutations in cDLBCL and to elucidate the role of such gene in the pathogenesis of this tumor. Mutations in POT1 were retrieved in 34% of cases, in line with previous reports, but no significant associations with any clinico-pathological variable were identified. Likewise, POT1 mutations are not predictive of worse prognosis. Interestingly, Ki-67 index was significantly higher in dogs harboring POT1 mutations compared to wild-type ones. These results suggest that POT1 mutations may exert their pathogenic role in cDLBCL by promoting cellular proliferation.